Low resting heart rates are associated with new-onset atrial fibrillation in patients with vascular disease: results of the ONTARGET/TRANSCEND studies - Boehm, M.; Schumacher, H.; Linz, D.; Reil, J. -C.; Ukena, C.; Lonn, E.; Teo, K.; Sliwa, K.; Schmieder, Roland; Sleight, P.; Yusuf, S. (Journal of Internal Medicine, 2015)
Elevated systolic blood pressure (SBP) and high resting heart rate (HR) are associated with cardiovascular end-points. Although the association between atrial fibrillation (AF) and SBP is well established, the relation between AF and HR remains unclear.In patients from the ONTARGET and TRANSCEND studies with high cardiovascular disease risk (n = 27 064), new-onset AF was evaluated in relation to mean SBP, visit-to-visit variation in SBP (SBP-CV; i.e. SD/mean × 100%), mean HR and visit-to-visit variation in HR (HR-CV).Low mean HR (P < 0.0001) and high SBP (P = 0.0021) were associated with incident AF. High SBP-CV (P = 0.031) and HR-CV (P < 0.0001) were also associated with incident AF. After adjustment for confounders, SBP and SBP-CV were no longer significantly associated with AF. The detrimental effect of low HR was particularly evident in subjects who were not receiving treatment with beta-blockers (P = 0.014 for interaction between beta-blocker use and mean HR). In addition to low HR, high HR-CV and high SBP had additive effects on incident AF.Low mean HR (<60 beats min(-1) ) is independently associated with incident AF, and low HR-CV and high SBP further increase the incidence of new-onset AF in patients at high risk of cardiovascular disease.
EVALuna2:3768